Spatio-temporal expression patterns of anandamide-binding receptors in rat implantation sites: evidence for a role of the endocannabinoid system during the period of placental development - Konje Justin C; Taylor Anthony H; Correia-; Fonseca Bruno M; Bell Stephen C; Teixeira Natércia A (BMC, 2009)
Abstract Background Although there is growing evidence that endocannabinoids play a critical role in early pregnancy, there are no studies describing the possible targets for this system after implantation. The endometrial stroma, which undergoes extensive proliferation and differentiation giving rise to the decidua and the trophoblast cells that invade after the initial stages of implantation, are potential targets. Since high anandamide (AEA) levels, the main endocannabinoid, are detrimental to implantation and in order to gain insight into the role of the endocannabinoid system in the development of the fetoplacental unit, the spatio-temporal pattern of expression of the anandamide-binding receptors, CB1, CB2 and the vanilloid receptor (TRPV1), were investigated by quantitative RT-PCR, western blot and immunohistochemistry. Methods Rat uterine maternal tissues from different days of pregnancy were used to investigate the expression of CB1, CB2 and vanilloid receptors by quantitative RT-PCR, western blot and immunohistochemistry. Results The data indicate that all the three receptors were expressed in decidualized cells and placenta. Interestingly, CB1 and CB2 were also expressed in smooth muscle cells of maternal blood vessels and in endovascular trophoblast cells, whereas TRPV1 was mainly expressed in uterine natural killer (uNK) cells and in the longitudinal muscle layer throughout pregnancy. In all tissues, CB2 protein was present at a lower level than CB1. Conclusion These observations support a role for the endocannabinoid system during the period of decidualization and placental development.